Psychological Therapies used for the reduction of habitual cigarette smoking cigarette consumption: A Systematic Review (2024)
Globally, there are around 1.3 billion cigarette consumers, indicating it to be the second highest risk factor for early death and morbidity. Meanwhile, psychological therapy offers tools based on its different models and techniques, which can contribute to smoking cessation. In this context, this study gathers scientific evidence to identify psychological therapies that can be used to reduce cigarette consumption. A systematic review of controlled clinical studies was conducted, implementing the PRISMA methodology. Search queries were performed with terms extracted from MESH (Medical Subject Headings) and DECS (Descriptors in Health Sciences). Subsequently, the search was queried in the scientific databases of Medline/PubMed, Cochrane, Scopus, Science Direct, ProQuest, and PsycNet, with subsequent verification of methodological quality using the Joanna Briggs Institute checklists. The selected documents revealed that cognitive behavioral therapy prevails due to its use and effectiveness in seven publications (25%). The cognitive approach with mindfulness therapy is found in 4 publications (14%), the transtheoretical model with motivational therapy in 4 publications (14%), brief psychological therapy in 3 publications (10%), and the remaining 10 documents (37%) correspond with others. Intervention studies refer to cognitive behavioral therapy as the most used in reducing cigarette consumption; in terms of the duration of abstinence, scientific evidence shows beneficial effects with short-term reduction.